Moral Distress and Moral Conflict in Clinical Ethics - Fourie, Carina (Bioethics, 2015)
Much research is currently being conducted on health care practitioners' experiences of moral distress, especially the experience of nurses. What moral distress is, however, is not always clearly delineated and there is some debate as to how it should be defined. This article aims to help to clarify moral distress. My methodology consists primarily of a conceptual analysis, with especial focus on Andrew Jameton's influential description of moral distress. I will identify and aim to resolve two sources of confusion about moral distress: (1) the compound nature of a narrow definition of distress which stipulates a particular cause, i.e. moral constraint, and (2) the distinction drawn between moral dilemma (or, more accurately, moral conflict) and moral distress, which implies that the two are mutually exclusive. In light of these concerns, I argue that the definition of moral distress should be revised so that moral constraint should not be a necessary condition of moral distress, and that moral conflict should be included as a potential cause of distress. Ultimately, I claim that moral distress should be understood as a specific psychological response to morally challenging situations such as those of moral constraint or moral conflict, or both.